Determination of the period of permanence of seedlings of Eucalyptus grandis W. Hill ex Maiden in greenhouse - Eloy, Elder; Caron, Braulio Otomar; Trevisan, Rômulo; Behling, Alexandre; Schmidt, Denise; Souza, Velci Queiróz de (Comunicata Scientiae, 2014)
This study aimed to determine the period the seedlings of Eucalyptus grandis W. Hill ex Maidenin a greenhouse using morphological parameters of height, stem diameter and total dry biomassand considering the current average daily increments. The experiment was conducted in thatexperimental design of blocks complete with split plots. The criterion were defined based on growthcurves and curves intercept between current increasing daily and daily average increase. Thevolume of substrate exploitable by the root system and the density of seedlings per tray influencedgrowth, noting that with larger seedlings are obtained in larger containers. The period the seedlingsin the nursery ranges 110-150 days, depending on the treatment used. The technical criterion usedto intercept between the curves of daily current increase and daily average increase is helpful indecision making, with a view to evaluate the standard of quality seedlings.